2020
DOI: 10.1002/pon.5474
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial characteristics of cancer‐related pain in patients attending specialist pain clinics in Australia and New Zealand

Abstract: BACKGROUND Opioids have been the mainstay of cancer pain relief for the past 40 years, but a multidimensional, biopsychosocial approach to assessment and treatment is now recommended. 1 The intensity of cancer pain and the distress it causes are well known, but it is less clear what patients with cancer think about their pain and how they cope with it. The electronic Persistent Pain Outcomes Collaboration (ePPOC) is an integrated pain outcomes center established in Australia and New Zealand (ANZ) in 2013 to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…These data are collected routinely at the time of referral for an initiative known as the electronic Persistent Pain Outcomes Collaboration (ePPOC). 13 Our analysis again found that pain-related distress and disability were common in these patients with cancer pain, in association with low pain self-efficacy and high pain catastrophizing scores. An acknowledged limitation of the analysis was the paucity of clinical information collected by ePPOC.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…These data are collected routinely at the time of referral for an initiative known as the electronic Persistent Pain Outcomes Collaboration (ePPOC). 13 Our analysis again found that pain-related distress and disability were common in these patients with cancer pain, in association with low pain self-efficacy and high pain catastrophizing scores. An acknowledged limitation of the analysis was the paucity of clinical information collected by ePPOC.…”
Section: Introductionsupporting
confidence: 60%
“…We previously analyzed data on pain intensity, pain outcomes and pain cognitions in a national sample of patients with cancer pain referred to hospital‐based multidisciplinary pain clinics in Australia and New Zealand. These data are collected routinely at the time of referral for an initiative known as the electronic Persistent Pain Outcomes Collaboration (ePPOC) 13 . Our analysis again found that pain‐related distress and disability were common in these patients with cancer pain, in association with low pain self‐efficacy and high pain catastrophizing scores.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…167 This correlation of increased pain severity and poor pain outcomes has been corroborated by other groups. 168 The impact of social constructs on pain and pain outcomes in cancer pain has been reported in a recent meta-analysis that identified that social support has been found to be associated with less postoperative pain after breast cancer surgery. 169 Furthermore, the presence of a strong social support network is associated with reduced cancer pain symptom burden, improved quality of life, and reduced distress in patients with chronic lymphocytic leukemia, 170 breast cancer, 171,172 and colorectal cancer.…”
Section: Cancer-related Painmentioning
confidence: 99%